A Novel Design of Mach-Zehnder Modulator Bias Controller Based on Pilot Tone Method. Issue 7 (April 2020) - Jin, Yucheng; Shi, Xiang; Zang, Chunhua; Chen, Zilong
Abstract: The Mach-Zehnder (MZ) modulator is a widely-used electro-optic modulator, but its operation point drifts with time and temperature, making the modulation performance worse. Therefore, a bias controller is needed to suppress drift. MZ modulator bias control method based on pilot analysis has good robustness and thus has many practical applications. However, many of the circuit designs based on the pilot method of the MZ modulator bias controller (MBC) are complicated, and the flexibility of the pilot generation is not satisfying. In response to these shortcomings, the paper introduces a new MZ modulator bias controller design. The bias controller uses the internal timer and DAC resources of the MCU to form a DDS generator instead of the traditional external oscillator, which makes the generation of the pilot frequency more flexible, and the signal conditioning circuit is improved. Test results show that the proposed MZ bias controller can achieve an extinction ratio of more than 30dB, and can finish the lock process at the Quad point within 20 seconds.